Association of brain-derived neurotrophic factor and dopamine D2 receptor gene single nucleotide polymorphisms in Malay obese attributes - Ramlah Farouk Muhammad; Universiti Sultan Zainal Abidin . Faculty of Medicine (2016)
Obesity epidemic occurs as a result of excessive energy intake and reduced energy expenditure. It shows continuous rise in prevalence globally and in Malaysia and the complexity in its pathogenesis make it an important area of study. Obesity is dependent on the interactions between genetic, environmental and behavioural factors. Polymorphisms in several genes have been associated with obesity. Among the several genes implicated in the pathophysiology of obesity are the brain derived neurotrophic factor (BDNF) and dopamine D2 receptor (DRD2) genes which play important roles in energy homeostasis and feeding behaviour, hence polymorphisms in these genes may predispose individuals to obesity. This study was aimed to investigate the association between Val66Met and DRD2 -141C Ins/Del polymorpbisms with obesity and its related parameters (body mass index, waist circumference, hip circumference, low density lipoprotein, high density lipoprotein, total cholesterol, atherogenic index of plasma, Castelli,s indices and atherogenic coefficient), determining the genotypic and allelic frequencies of BDNF Val66Met and DRD2 -141C Ins/Del SNPs in Malay subjects and the presence or lack of synergistic effect between these SNPs. A total of 223 subjects were studied. Following DNA extraction, the SNPs were genotyped using polymerase chain reaction-restriction fragment length polymorphism technique (PCRRFLP) and visualized using UV transilluminator. Lipid profiles were estimated. Data were analysed using SPSS 20.0 statistical software and SHEsis online version. BDNF Val66Met and DRD2 -141C Ins/Del showed association with obesity by having a p-value 0.0016 and 0.004 and trending towards susceptibility with OR of l.856 and l.6442 respectively. After correcting for age and sex, significant associations were exhibited between -141 C Ins/Del SNP with triglyceride, high density lipoprotein, atherogenic plasma index, Castelli's indices I and II and atherogenic coefficient. Val66Met and DRD2 -141C Ins/Del polymorphisms had low linkage disequilibrium. The haplotypes 111 and 211 obtained for both Val66Met and DRD2 -]41C Ins/Del polymorphisms showed association with obesity, with haplotype I/I being susceptible to obesity while 211 exerted protective function against obesity. Therefore it can be concluded that association exist between BDNF Val66Met and DRD2-141 C InsiDel polymorphisms in obese Malays.
1. Introduction -- 2. Literature review -- 3. Materials and methods -- 4. Results -- 5. Discussion -- 6. Conclusion
Thesis (Degree of Master of Science) - Universiti Sultan Zainal Abidin, 2016
Includes bibliographical references (leaves 99-125)
Keywords: Universiti Sultan Zainal Abidin -- Dissertations; Universiti Sultan Zainal Abidin -- Faculty of Medicine -- Dissertations; Brain-Derived Neurotrophic Factor; Dopamine; Neurons -- Growth; Neurophysiology; Neurotrophic functions; Nucleotides; Obesity; Dissertations, Academic